Tenebrio molitor Frass: A Cutting-Edge Biofertilizer for Sustainable Agriculture and Advanced Adsorbent Precursor for Environmental Remediation - Alessandra Verardi; Paola Sangiorgio; Brigida Della Mura; Stefania Moliterni; Anna Spagnoletta; Salvatore Dimatteo; Daniela Bassi; Claudia Cortimiglia; Raffaella Rebuzzi; Salvatore Palazzo; Simona Errico (Agronomy)
The projected growth of the global population to over 10 billion by 2080 necessitates groundbreaking sustainable agricultural solutions that enhance productivity while mitigating environmental impacts. Tenebrio molitor frass (TMF), derived from larval excrement and exuviae, has emerged as a promising organic fertilizer. Enriched with macro- and micronutrients, TMF enhances soil functions through microbial communities that promote nutrient cycling, decompose organic matter, and suppress soilborne pathogens. Additionally, functional compounds like chitin, cellulose, xylans, and lignin improve the soil structure, foster beneficial microbes, and activate natural plant defence responses. The synergy of microbial activity and bioactive compounds positions TMF as a valuable resource for enhancing plant growth and soil health. Its role as a nutrient source, biostimulant, and soil amendment aligns with circular economy principles by recycling agro-industrial by-products and reducing reliance on synthetic fertilizers. TMF also contributes to sustainable agriculture by improving soil fertility, microbial biodiversity, and plant stress resilience, while mitigating greenhouse gas emissions and nutrient runoff. Additionally, TMF-derived biochar offers the potential for environmental remediation as an effective adsorbent. Despite its advantages, TMF faces challenges in scalability, cost, and regulations, requiring advancements in processing, enrichment, and supportive policies to maximize its potential in sustainable farming.